Gene Mutation Patterns of Rifampicin in Multidrug - Resistant Mycobacterium Tuberculosis Complex Strains - Yıldırım Servi, Esra; Uzun, Meltem; Yıldırım Servi, Esra; Uzun, Meltem (Istanbul University Press, 2022)
Objective: The aim of this study was to evaluate the GenoType®MTBDRplus test for detection of rifampicin (RIF) resistance in MDR Mycobacterium tuberculosis complex strains. Materials and Methods: Twenty-five multidrug-resistant (MDR) Mycobacterium tuberculosis clinical strains were used, gene mutations causing RIF resistance were investigated by GenoType®MTBDRplus and the results were compared with the results of the BACTEC 460 TB system. The strain was sequenced if there was no mutation and absence Wild Type (WT). Mycobacterium tuberculosis ATCC 35838 was used as a quality control (QC) strain. Results: There was 96% compliance between the GenoType®MTBDRplus and BACTEC 460 TB system for the finding of RIF resistance. The most frequent mutation zone in MDR strains was rpoB S531L promotor zone (13 strains, 52%). The other rpoB gene mutations were H526Y (three strains, 12%) and H526D (three strains, 12%), while five strains (20%) had Δ2-Δ5 mutations in the wild type probes. There was no mutation in only one strain (4%) by GenoType®MTBDRplus but it was found to be as resistant to rifampicin by the BACTEC 460 TB system. This strain was sequenced and detected to have triple mutations. Mutations were found on codons 489, 493, and 503. Conclusion: GenoType®MTBDRplus showed good compatibility with the BACTEC 460 TB system in detecting rifampicin resistance, and it was thought that GenoType®MTBDRplus could be an effective and reliable test for RIF susceptibility testing in MDR-TB patients, providing a significant advantage in technical time.

Amaç: Bu çalışmada, çoğul ilaca dirençli (ÇİD) Mycobacterium tuberculosis kompleks suşlarında rifampisin (RIF) direncinin saptanmasında GenoType®MTBDRplus testinin değerlendirilmesi amaçlanmıştır. Gereç ve Yöntem: Yirmi beş ÇİD Mycobacterium tuberculosis klinik suşu kullanılmış, RIF direncine neden olan gen mutasyonları GenoType®MTBDRplus ile araştırılmış ve sonuçlar BACTEC 460 TB sistemi sonuçları ile karşılaştırılmıştır. Eğer mutasyon veya Vahşi Tip (VT) bandı yoksa suş sekanslanmıştır. Kalite kontrol (QC) suşu olarak Mycobacterium tuberculosis ATCC 35838 kullanılmıştır. Bulgular: Rifampisin direncinin saptanmasında GenoType®MTBDRplus ve BACTEC 460 TB sistemi arasında %96 uyum bulunmuştur. ÇİD suşlarda mutasyonun en sık rpoB S531L promotor bölgede (13 suş, %52) olduğu görülmüştür. Diğer rpoB gen mutasyonları H526Y (üç suş, %12) ve H526D (üç suş, %12) bölgesinde iken, beş suşta (%20) vahşi tip problarında Δ2-Δ5 mutasyonları saptanmıştır. Bir suşta (%4) GenoType®MTBDRplus ile mutasyon bulunamamış, ancak BACTEC 460 TB sistemi ile rifampisine dirençli olduğu belirlenmiştir. Bu suş sekanslanmış, 489, 493 ve 503 kodonlarında üçlü mutasyona sahip olduğu tespit edilmiştir. Sonuç: Rifampisin direncinin saptanmasında GenoType®MTBDRplus, BACTEC 460 TB sistemi ile iyi uyum göstermiştir ve ÇİDTB hastalarında RIF duyarlılık testi için GenoType®MTBDRplus’ın etkili ve güvenilir bir test olabileceği ve bunun teknik zaman açısından da önemli bir avantaj sağlayacağı düşünülmüştür
Çoğul İlaca Dirençli Mycobacterium Tuberculosis Kompleks Suşlarında Rifampsinin Gen Mutasyon Paternleri
Keywords: GenotypeMTBDRplus; Mycobacterium; Resistance; Rifampicin; RpoB; Tuberculosis; Tüberküloz; Rifampisin; Direnç